Practical Work on the Implementation Evaluation of Occupational Safety and Health Procedures at Zainuddin Abdul Madjid International Airport. - Suripto; Wahyuni; Maria Carolina Lopulalan (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
The program of occupational safety and sealth (POSH) is a program that should exist in every public service agency, including international airports which are service centers for the entry and exit of people or goods from/and out of the country. Zainuddin Abdul Madjid International Airport (ZAMIA) has the equipment and facilities to carry out POSH implementation. The student practical work program has been done at ZAMIA with the aim that students can gain knowledge and field work skills in evaluating POSH implementation and studying the factors that influence the effectiveness of POSH implementation in ZAMIA operational area. This work practice has been carried out by following direct investigations, interviews and discussions with relevant officers to collect primary data and conducting searches of literatures and related documents to collect secondary data as well as attending meetings related to data analysis and evaluation of POSH implementation in ZAMIA. The results show that after carrying out practical work, students gain knowledge and skills about POSH implementation, investigating evidence of events in the field and processing data to evaluate POSH implementation at ZAMIA. There were 498 incidents reported from January to July 2024, of which more than 90% were events with hazard criteria and less than 10% were normal events (incidents). In ZAMIA, there are 12 categories of incidents that are the object of mandatory reporting, namely kites, drones, wildlife animals, weather, runway surface damage, malfunctioning airfield lighting, laser attacks, FOD, bird strikes, aircraft trouble and others. Of the 12 categories of incidents, the top 5 categories of hazard events were recorded, namely equipment/facility damage, wildlife animal and bird strikes, laser attacks, FOD and bad weather